Patrimônio ferroviário e refuncionalização dos bens culturais tombados da companhia paulista de estradas de ferro (CPEF) - Maria Tereza Duarte Paes; Rafael Henrique de Moura (Confins)
This paper results from the analysis of railway stations that belong to the Companhia Paulista de Estradas de Ferro (CPEF) located in São Paulo, SP, Brazil, with emphasis on their refunctionalization, since they are part of the state’s cultural heritage. The methodology of the study comprised an analysis of the state’s processes of listed pieces of real estate, a literature review and results of field work. The first section deals with general remarks about cultural heritage and two of its typologies, i. e., industrial heritage and railway heritage. Afterwards, to contextualize railway activities, it introduces railways as dynamic agents that formed São Paulo state. The second section highlights the council that defends the state’s historical heritage, i. e., the Conselho de Defesa do Patrimônio Histórico, Arqueológico, Artístico e Turístico do Estado de São Paulo (Condephaat) and listing of railway assets. Taking into consideration that railway stations are the most expressive cultural assets in this typology in the state and in the country, this study aims at reflecting upon the role of their listing, changes in the conception of preservation of isolated assets to valorize the railway complex in the territory and landscape context, refunctionalization of railway stations that comprise the CPEF’s remaining cultural heritage and its new social uses.